2022
DOI: 10.3389/fpsyt.2022.1071563
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between thyroid hormone and sex hormone levels and non-suicidal self-injury in male adolescents with depression

Abstract: ObjectiveNon-suicidal self-injury (NSSI) is the intentional and repeated direct injury to one’s bodily tissues or organs without the intent to die, which is not socially sanctioned and does not result in death. This study will be the first to explore the relationship between NSSI behavior and thyroid hormone and sex hormone levels in male adolescents with depression.MethodsAmong the inpatients in the children’s ward of Shandong Mental Health Center, eighty male patients with first-episode depressive disorder w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…This endeavor stems from the existing scarcity of dependable biomarkers in this domain. The association between thyroid dysfunction and depression has long been established, with some experts postulating that thyroid hormones may be involved in the underlying neurobiological mechanisms of suicidal behavior [15]. Additionally, several studies have reported a correlation between lipid abnormalities and suicidality [16].…”
Section: Introductionmentioning
confidence: 99%
“…This endeavor stems from the existing scarcity of dependable biomarkers in this domain. The association between thyroid dysfunction and depression has long been established, with some experts postulating that thyroid hormones may be involved in the underlying neurobiological mechanisms of suicidal behavior [15]. Additionally, several studies have reported a correlation between lipid abnormalities and suicidality [16].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive meta-analysis of 12,315 individuals indicated that patients with subclinical hypothyroidism have a higher risk of depression compared to euthyroid controls (relative risk of 2.35, 95% CI: 1.84 to 3.02, p < 0.001) ( 7 ). Depression-related thyroid hormone (TH) level changes include increased reversed triiodothyronine (rT3) ( 8 , 9 ) and decreased circulating T3 and TSH levels ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…This endeavor stems from the existing scarcity of dependable biomarkers in this domain. The association between thyroid dysfunction and depression has long been established, with some experts postulating that thyroid hormones may be involved in the underlying neurobiological mechanisms of suicidal behavior ( 9 ). Additionally, several studies have reported a correlation between lipid abnormalities and suicidality ( 10 ).…”
Section: Introductionmentioning
confidence: 99%